The impact of growth, energy and financial development on the environment in China: A cointegration analysis - Jalil, Abdul; Feridun, Mete (Elsevier, 2011)
This article aims to investigate the impact of financial development, economic growth and energy consumption on environmental pollution in China from 1953 to 2006 using the Autoregressive Distributed Lag (ARDL) bounds testing procedure. The main objective is to examine the long run equilibrium relationship between financial development and environmental pollution. The results of the analysis reveal a negative sign for the coefficient of financial development, suggesting that financial development in China has not taken place at the expense of environmental pollution. On the contrary, it is found that financial development has led to a decrease in environmental pollution. It is concluded that carbon emissions are mainly determined by income, energy consumption and trade openness in the long run. Moreover, the findings confirm the existence of an Environmental Kuznets Curve in the case of China. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Growth; Financial development; CO2 emission; Energy consumption